Problem-Based Learning Strategy in Improving Students’ Skill in Performing a Speech - Hilmiyah Akib; Abd. Rauf Ibrahim (Inspiring: English Education Journal, 2018)
This study focused on students’ skill in performing a speech and had conducted based on the problem. The students think performing a speech is the difficult thing, the students think there are problems appear when the students perform a speech in front of the people, suddenly forgetting the script, getting anxious, and getting blank. The researcher considered to conduct this study when doing observation at MAN 2 Parepare since the students showed fair competence in performing a speech. The objective of the study is to give some abilities and knowledge in this case Contextual Teaching and Learning that focused in Problem-based. The study applied quasi-experimental design, with two groups namely experimental class and control class. The populations of the study were the twelfth grade students at MAN 2 Parepare where the total numbers were 84 students. The samples of the study were consisted of 39 students. The result showed that the students’ skill in performing a speech of the twelfth grade students of MAN 2 Parepare could be improved through Problem-Based Learning Strategy. In performing s speech, the speakers need to be brave, except having some abilities in performing a speech.